Fabrication of larynx-shape tissue engineered cartilage by means of filling together with wrapping with pedicle myofascial flap - Sun, An-ke; Li, Wan-tong; Meng, Qing-yan; Liu, Song-bo; Chen, Wei; Tang, Wei-wei (Zhonghua er bi yan hou tou jing wai ke za zhi = Chinese journal of otorhinolaryngology head and neck surgery, 2011)
To explore the method of fabricating larynx-shape tissue engineered cartilage by means of filling together with wrapping with pedicle myofascial flap. Serial steps of solution casting, extrusion molding and particulate leaching were used to make larynx-shape [poly (3-hydroxybutyrate-co-3-hydroxyhexanoate), PHBHH] biomaterial models. The chondrocytes were seeded onto PHBHH models to form cell-PHBHH composites for culture in vitro for one week and then to fill and wrap larynx-shape composites with pedicle myofascial flap. After that to implant larynx-shape composites in situ on the back of adult New Zealand white rabbits (experimental groups n = 9). Control groups (n = 3) were the same measure as experimental groups but without chondrocytes on PHBHH models. Finally, morphological observation, HE & special staining and immunohistochemical test were conducted to evaluate the cartilage regeneration and its shape at 6, 8 and 12 weeks following implantation. The PHBHH models appeared to be hollow half-trumpet with e